2018
DOI: 10.1101/494252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving cell cycle speed in one snapshot with a live-cell fluorescent reporter

Abstract: Cell proliferation changes concomitantly with fate transitions during reprogramming, differentiation, regeneration, and oncogenesis. Methods to resolve cell cycle length heterogeneity in real-time are currently lacking. Here, we describe a genetically encoded fluorescent reporter that captures live cell cycle speed using a single measurement. This reporter is based on the color-changing Fluorescent Timer (FT) protein, which emits blue fluorescence when newly synthesized before maturing into a red fluorescent p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 84 publications
(102 reference statements)
2
9
0
Order By: Relevance
“…In the first 26 hours of culture, the difference in growth rate for the Bcl-xL-Epor -/and EpoR-Epor -/cultures indicated a substantial difference in doubling time, of 6.1 h for EpoR-Epor -/erythroblasts, compared with 8.6 h for Bcl-xL-Epor -/erythroblasts (95% confidence intervals: 5.6 to 7.1 h and 7.7 to 10.4 h, respectively ; Fig 2c, e). A cycle length of 6 hours for EpoR-Epor -/is in good agreement with our recent direct measurement of a 6 hour cell cycle duration in early erythroblasts in vivo 27 , and with an independent measurement using a fluorescent timer protein that found early erythroblasts to have the shortest cell cycle amongst bone marrow hematopoietic progenitors 28 .…”
Section: Erythroblasts Undergo Fewer and Slower Cell Cycles In The Absupporting
confidence: 89%
See 3 more Smart Citations
“…In the first 26 hours of culture, the difference in growth rate for the Bcl-xL-Epor -/and EpoR-Epor -/cultures indicated a substantial difference in doubling time, of 6.1 h for EpoR-Epor -/erythroblasts, compared with 8.6 h for Bcl-xL-Epor -/erythroblasts (95% confidence intervals: 5.6 to 7.1 h and 7.7 to 10.4 h, respectively ; Fig 2c, e). A cycle length of 6 hours for EpoR-Epor -/is in good agreement with our recent direct measurement of a 6 hour cell cycle duration in early erythroblasts in vivo 27 , and with an independent measurement using a fluorescent timer protein that found early erythroblasts to have the shortest cell cycle amongst bone marrow hematopoietic progenitors 28 .…”
Section: Erythroblasts Undergo Fewer and Slower Cell Cycles In The Absupporting
confidence: 89%
“…First, erythroblasts underwent slower and fewer cell cycles, generating far fewer red cells, showing that EpoR is essential for the rapid cycling of early erythroblasts. We confirmed this using a mouse transgenic for a fluorescent reporter of cell cycle length, finding that Epo stimulation shortened cell cycle length in vivo in early erythroblasts, cells that are already amongst the fastest cycling cells in the bone marrow 27,28 . Second, we found that, unexpectedly, despite its stimulation of rapid erythroblast cycling, EpoR signaling increases cell size in both erythroblasts and red cells.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Analysis of 100 proteins in human cancer cells revealed that the abundance of proteins with a long half‐life depends on dilution through cell division . Indeed, the concept that stable proteins are preferentially retained in slow‐dividing or nondividing cells could be recapitulated by transgenically expressed reporter proteins . These data support the hypothesis that cell cycle length can be opted to control and alter the concentration of molecular species dependent on their inherent half‐lives.…”
Section: Potential Molecular Consequences Of Rapid Cell Cyclementioning
confidence: 71%